Legal Studies on the Practice of Protecting the Right to Health Adolescent Reproduction in Tuatuka Village - Yetrim Inang Sula; Trihoni Nalesti Dewi; Hartanto Hartanto (Soepra Jurnal Hukum Kesehatan, 2022)
Abstract։ The condition of adolescent reproductive health is very important, the state must provide sources or channels that can be accessed by adolescents in fulfilling their rights to obtain adequate information and reproductive health services so as to avoid misleading information. This study aims to determine the regulation and implementation of the protection of adolescent reproductive health rights in Tuatuka Village. This study uses a sociological juridical approach. Data were obtained through interviews with parties from the Kupang District Health Office, Kupang District Education Office, Kupang District Ministry of Religion Office, Oesao Health Center, Tuatuka Sub-district Health Center, the community, parents and youth in Tuatuka Village. Data were analyzed qualitatively. The implementation of the fulfillment of adolescent reproductive health rights is carried out based on the provisions of regulations at the national level as outlined in the Minister of Health Regulation Number 4 of 2019 concerning Technical Standards for Fulfilling Basic Service Quality in Minimum Service Standards in the Health Sector, there are no regional policies related to adolescent reproductive health in the Kupang Regency area. Protection of adolescent reproductive health rights is more inclined to preventive protection efforts. Preventive efforts are carried out through screening students in schools, namely carrying out UKS, BIAS and TTD activities carried out by health center midwives. In a curative effort, the Kupang District Health Office has not fully made efforts to improve supervision in the implementation of the Adolescent Reproductive Health Service (PKPR) program available at the puskesmas, because the program has not been utilized by adolescents. Keywords: Legal Protection, Youth, Adolescent Reproductive Health Rights Abstrak: Kondisi kesehatan reproduksi remaja sangat penting, negara harus menyediakan sumber atau saluran yang dapat diakses oleh remaja dalam memenuhi haknya memperoleh informasi dan pelayanan kesehatan reproduksi yang memadai sehingga terhindar dari informasi yang menyesatkan. Penelitian ini bertujuan untuk mengetahui pengaturan dan pelaksanaan perlindungan hak kesehatan reproduksi remaja di Kelurahan Tuatuka. Penelitian ini menggunakan pendekatan yuridis sosiologis. Data diperoleh melalui wawancara dengan pihak-pihak dari Dinas Kesehatan Kabupaten Kupang, Dinas Pendidikan Kabupaten Kupang, Kantor kementerian Agama kabupaten Kupang, Puskesmas Oesao, Puskesmas Pembantu Tuatuka, masyarakat, orang tua dan remaja di Kelurahan tuatuka. Data dianalisis secara kualitatif. Pelaksanan pemenuhan hak kesehatan reproduksi remaja dilakukan berdasarkan ketentuan peraturan di tingkat nasional yang terjabarkan dalam Peraturan Menteri Kesehatan Nomor 4 Tahun 2019 tentang Standar Teknis Pemenuhan Mutu Pelayanan Dasar Pada Standar Pelayanan Minimal Bidang Kesehatan, belum ada kebijakan daerah terkait kesehatan reproduksi remaja di wilayah Kabupaten Kupang. Perlindungan hak kesehatan reprduksi remaja lebih cenderung kepada upaya perlindungan preventif. Upaya preventif, dilaksanakan melalui penjaringan siswa-siswi di sekolah yaitu melakukan kegiatan UKS, BIAS dan TTD yang dijalankan oleh bidan puskemas. Dalam upaya kuratif, Dinas Kesehatan Kabupaten Kupang belum sepenuhnya melakukan upaya perbaikan terkait pengawasan dalam pelaksanaan program Pelayanan Kesehatan Reproduksi Remaja (PKPR) yang tersedia di puskesmas, karena program tersebut belum belum dimanfaatkan oleh remaja. Kata kunci: Perlindungan Hukum, Remaja, Hak Kesehatan Reproduksi Remaja